A history of the Faculty of Arts at the University of Adelaide 1876-2012 celebrating 125 years of the Faculty of Arts - Harvey, Nick 1952-; Fornasiero, Jean; MacCarthy, Greg; Macintyre, Clem; Crossin, Carl (The University of Adelaide Press, 2012)
Even though the BA was the first degree it was not until eight years later in 1887 that the Faculty of Arts was inaugurated. In the first 50 years of the Universitys existence, less than ten BA students graduated each year. At the start of the 21st century this figure had climbed to over 300 BA graduates per year but what is interesting is that by 2010 the number of BA graduates was equalled by the number of graduates from separate named degrees within the Faculty plus 70 Music graduates
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: University of Adelaide / Faculty of Arts / History; University of Adelaide; Geschichte 1876-2012; Geschichte; Sozialwissenschaften; Humanities / Study and teaching (Higher) / Australia / Adelaide (S.A.) / History; Social sciences / Study and teaching (Higher) / Australia / Adelaide (S.A.) / History; Arts / Study and teaching (Higher) / Australia / Adelaide (S.A.) / History; Universities and colleges / Australia / Adelaide (S.A.) / Departments / History; Geisteswissenschaften; Australien